Assessment of gestational age in goats by Real-Time Ultrasound measuring the fetal crown rump length, and bi-parietal diameter - Rasheed, Yaseen Mahmood (The Iraqi Journal of Veterinary Medicine, 2018)
The aim of the present study was to specify the relationship of gestational period with measurement of Crown-Rump length and Bi-parietal diameter via trans-abdominal ultrasonography in goats. This study was conducted in the Faculty of Veterinary Medicine in Diyala University. The study was carried out on twelve multiparous does, their ages were between 2-5 years. Does were synchronized for estrus with PGF2α (Estrumate) at 11 days apart and naturally served to obtain pregnancy (estrus day=day 0), and subsequently Ultrasonic scanned. Weekly ultrasonographic examinations were performed using 3.5-5MHz sector transducer, from week (5-10) and (6-14) of pregnancy for measuring the Crown-Rump length and Bi-parietal diameter, respectively. The results clearly demonstrated that the relationship between gestational age and Crown-Rump length or Bi-parietal diameter were highly significant (P<0.01). The Crown-Rump length was strongly positively correlated with gestational age (R2=0.99) followed by the Bi-parietal diameter (R2=0.95). In conclusion, the gestational age of goats can be accurately estimated by trans-abdominal ultrasonography measuring of fetal Crown-Rump length and Bi-parietal diameter during first and second trimester of pregnancy.